Extracorporeal adsorption of anti-Factor VIII allo-antibodies on randomly functionalized polystyrene resins - Huguet, Hélène-Céline; Lasne, Dominique; Rothschild, Chantal; Siali, Rosa; Jozefonvicz, Jacqueline (Thrombosis and Haemostasis, 2004)
The occurrence of anti-factor VIII (FVIII) allo-antibodies is a severe complication of the treatment of haemophilia A patients, leading to the inhibition of transfused FVIII activity. The effective elimination of these inhibitory antibodies plays a decisive role in the management of affected patients. To achieve this, immunoadsorption devices employing synthetic adsorbers, which selectively eliminate inhibitors, are of interest in the treatment strategy of haemophilia A patients with inhibitors. Adsorbers consisting of polystyrene-based beads substituted with sulphonate and L-tyrosyl methylester groups, which mimic part of epitope of FVIII molecule recognized by inhibitors, exhibit selective binding capacities towards anti-FVIII antibodies. The adsorption of FVIII inhibitors was investigated by simulating an extracorporeal circulation of haemophilic plasma over these functionalized resins. These innovative adsorbers are able to remove around 25% of anti-FVIII antibodies in 15 minutes depending on the plasma tested. Furthermore, they do not modify the amount of essential plasmatic proteins or residual immunoglobulins G. Experiments which were carried out using different plasmas with various inhibitor titres demonstrate a good reproducibility regarding the adsorption capacity of the synthetic resin. The characteristics of adsorption are similar on either native or regenerated resins. Both the purely synthetic nature of the resin and its easy processability demonstrate the real advantages over currently available protocols. This synthetic adsorber is a major technological advance in selective removal of FVIII inhibitory antibodies.
Keywords: Anti-FVIII inhibitors; functionalized adsorbers; haemophilia A; immunoadsorption; extracorporeal circulation